Law on Domestic Violence Prevention and Control - The National Assembly (2007)
This Law provides for domestic violence prevention, protection of and support for domestic violence victims; responsibilities of individuals, families, agencies and organizations in domestic violence prevention and control; and handling of violations concerning domestic violence prevention and control. Domestic violence means an intentional act by a family member which causes or potentially causes physical, spiritual and financial damage to other members of a family